Space as designs for and in learning: investigating the interplay between space, interaction and learning sequences in higher education - Leijon, Marie (Visual communication (London, England), 2016)
In this article, the author seeks to investigate the interplay between space, interaction and learning sequences in higher education. She argues that space is an important part of designs for learning, where the building and the rooms are parts of the framing and the conditions for learning; furthermore, she discusses space as a resource in the meaning-making process, considering space as a significant part of designs in learning. The analysis builds on the concept that we can read space as three-dimensional text, using Halliday’s metafunctional theory to understand meaning potential in a space. The article also draws on a design-oriented perspective called ’Designs for Learning’ and demonstrates how we can understand space as being a part both of designs for learning and of designs in learning.